Direct Detection of Ultraweak CO Signal with Cavity Plasmon by Resonant Vibration–Plasmon Coupling. Issue 10 (6th September 2020) - Yang, Da‐Jie
Abstract: Direct, instant, and quantitative detection of molecules is highly desirable, however, optical detection of dilute gas molecules in the single molecular limit is extremely challenging. According to a recent experiment, a thin CO molecule layer will be absorbed at the edge of a metallic nanoparticle when the particle is exposed to CO environment; therefore, optical sensor becomes possible with such a layer. Here, a prototype plasmonic sensor for direct CO molecules detection based on the vibrational coupling to the surface plasmon polariton resonance in a finite metal/insulator/metal (MIM) nanocavity is proposed and investigated. Thanks to the ultrahigh spectral sensitivity of the cavity plasmon and its enhanced coupling to the CO stretch vibration, the single‐layered molecules in the cavity split the plasmon resonance in its optical spectra. The molecular signal is amplified by up to three orders of magnitude, giving a detection limit of ≈800 molecules, which lowers down the detection limit of molecule numbers by more than three orders of magnitude than the traditional surface plasmon‐based sensors. In the investigation, analytical vibration/cavity–plasmon coupling model developed herein agrees well with the numerical results. The study offers a promising way toward small molecule detection with plasmonic sensors. Abstract : Ultraweak CO (800 molecules) vibrational signals in the infrared range is detected with cavity plasmon by resonant vibration–plasmon coupling. The molecular signal is amplified by up to three orders of magnitude, giving a detection limit of ≈800 molecules, which lowers down the detection limit of molecule numbers by more than three orders of magnitude than the traditional surface plasmon‐based sensors.